Students' perception of attributes of independent colleges of business profile in the market of higher education in Poland = Percepcja atrybutów uczelni niepublicznych o profilu biznesowym przez studentów na rynku szkolnictwa wyższego w Polsce - Dejnaka, Agnieszka; Kulig-Moskwa, Katarzyna; Łobos, Krzysztof; Nogieć, Joanna; Szewczyk, Mirosława (Zielona Góra: Faculty of Economics and Management Press)
The article examines the general attributes which are in use by clients (students) in the process of evaluation of non-public colleges of business profile in Poland. The evaluations are presented in comparison with other academic institutions having the same profile, both independent and public ones.
Keywords: wartości akademickie; wartości praktyczne; pokolenie; oczekiwania studentów; rynek edukacji wyższej w Polsce; academics; practical; generations; students expectations; market of higher education in Poland